Pelatihan Tips & Trik TOEFL Organisasi Komunitas Kreativitas Mahasiswa Intelektual (KAMI) - Hasnani; Rezki Lili (Yayasan Habiburrahman Jamalu Bina Ummat, 2023)
Global competition in various fields demands adequate and accountable skill and academic competence expertise. In the world of education, various efforts have been tried to prepare for this global competition, which is very meaningful to produce graduates who are able to compete to continue to the Learning level and in the world of work. The goal to be achieved in this Community Service activity is to provide effective integrated TOEFL Tips & Tricks Training to improve English mastery skills for OUR Organization Members. At the beginning of the activity, participants conducted a pre-test with test material for TOEFL Tips & Tricks Training test. The training is divided into three basic skills, namely, Listening, Structure and Written Expression, and Reading Comprehension. Listening and Reading material is given in three training sessions, while Structure & Written Expression material is given in four meeting sessions. Each session is held for 90 minutes with a balance of theory and practice in the form of doing practice questions. The results of this community service activity received a positive response from the D4 Medical Laboratory Technology Study Program as the Study Program that houses OUR Organization. The form of positive response can be seen, among others, from active participation, both from the head of the Study Program and the administrators of our Organization as well as from the training participants.